2022
DOI: 10.1371/journal.pgen.1009977
|View full text |Cite
|
Sign up to set email alerts
|

A locus at 19q13.31 significantly reduces the ApoE ε4 risk for Alzheimer’s Disease in African Ancestry

Abstract: African descent populations have a lower Alzheimer disease risk from ApoE ε4 compared to other populations. Ancestry analysis showed that the difference in risk between African and European populations lies in the ancestral genomic background surrounding the ApoE locus (local ancestry). Identifying the mechanism(s) of this protection could lead to greater insight into the etiology of Alzheimer disease and more personalized therapeutic intervention. Our objective is to follow up the local ancestry finding and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…Both variants were assessed in Europeans, due to the paucity of variant carriers in non-European ancestries. Another recent study identified a variant proximal to the APOE region, reducing the APOE -ε4 risk for AD in African Ancestry 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Both variants were assessed in Europeans, due to the paucity of variant carriers in non-European ancestries. Another recent study identified a variant proximal to the APOE region, reducing the APOE -ε4 risk for AD in African Ancestry 9 .…”
Section: Introductionmentioning
confidence: 99%
“…3 An important caveat to broad interpretation of this work is that AD and AMD risk vary across ancestry, as does APOE-specific AD risk. 6,7 In AD and AMD, studies in recent years have expanded focus beyond samples of primarily European descent to examine more diverse populations and have found major differences in wellknown disease-associated variants. A notable example of the importance of diversity was recently reported, in which the effect of the APOE ε4 allele in a population sample of primarily African ancestry was seemingly modified by a second locus (rs10423769), upstream of APOE.…”
mentioning
confidence: 99%
“…Although the population sample evaluated was large (>100 000), all participants were of European descent, despite the fact that the rare variant motivating the work was discovered in a Colombian sample . An important caveat to broad interpretation of this work is that AD and AMD risk vary across ancestry, as does APOE -specific AD risk . In AD and AMD, studies in recent years have expanded focus beyond samples of primarily European descent to examine more diverse populations and have found major differences in well-known disease-associated variants.…”
mentioning
confidence: 99%
See 2 more Smart Citations